A recursive microfluidic platform to explore the emergence of chemical evolution - Doran, David; Rodriguez-Garcia, Marc; Turk-MacLeod, Rebecca; Cooper, Geoffrey J. T.; Cronin, Leroy (Beilstein Journal of Organic Chemistry, 2017)
We propose that a chemically agnostic approach to explore the origin of life, using an automated recursive platform based on droplet microfluidics, could be used to induce artificial chemical evolution by iterations of growth, speciation, selection, and propagation. To explore this, we set about designing an open source prototype of a fully automated evolution machine, comprising seven modules. These modules are a droplet generator, droplet transfer, passive and active size sorting, splitter, incubation chamber, reservoir, and injectors, all run together via a LabVIEWTM program integration system. Together we aim for the system to be used to drive cycles of droplet birth, selection, fusion, and propagation. As a proof of principle, in addition to the working individual modules, we present data showing the osmotic exchange of glycylglycine containing and pure aqueous droplets, showing that the fittest droplets exhibit higher osomolarity relative to their neighbours, and increase in size compared to their neighbours. This demonstrates the ability of our platform to explore some different physicochemical conditions, combining the efficiency and unbiased nature of automation with our ability to select droplets as functional units based on simple criteria.
Keywords: artificial life; autocatalysis; automated platforms; chemical evolution; evolution before genes; evolution first; microfluidics